Treatment of chronic kidney diseases with histone deacetylase inhibitors - Liu, Na; Zhuang, Shougang (Frontiers in Physiology, 2015)
Histone deacetylases (HDACs) induce deacetylation of both histone and non-histone proteins and play a critical role in the modulation of physiological and pathological gene expression. Pharmacological inhibition of HDAC has been reported to attenuate progression of renal fibrogenesis in obstructed kidney and reduce cyst formation in polycystic kidney disease. HDAC inhibitors (HDACis) are also able to ameliorate renal lesions in diabetes nephropathy, lupus nephritis, aristolochic acid nephropathy and transplant nephropathy. The beneficial effects of HDACis are associated with their anti-fibrosis, anti-inflammation, and immmunosuppressant effects. In this review, we summarize recent advances on the treatment of various chronic kidney diseases with HDACis in preclinical models.